2022
DOI: 10.3233/cbm-210533
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic efficacy of the new prospective biomarker’s combination CA 15-3 and CA-62 for early-stage breast cancer detection: Results of the blind prospective-retrospective clinical study

Abstract: BACKGROUND: Combination of different cancer markers is often used for predicting tumor growth, for the response to cancer therapy, and for increase in the positive diagnosis ratio in the malignant tumors. OBJECTIVE: Evaluation of the diagnostic efficacy of CA 15-3 and CA-62 cancer markers combination for early stages of breast cancer (BC) detection. METHODS: This retrospective blind study was performed on 2 clinically validated Sets that included serum measurements of CA 15-3 ELISA and CLIA-CA-62 assays in 488… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…На клеточной мембране таких низкодифференцированных мезенхимальных стволовых клеток с самого начала канцерогенеза в больших количествах образуется сильно гликозилированный гликопротеин СА-62, который попадает в кровь с поверхности клеток на самых ранних стадиях рака, включая карциномы in situ, и детектируется при помощи ИХА-СА-62 хемилюминесцентного иммуноанализа. Более ранние исследования показали, что злокачественные клетки демонстрируют значительную экспрессию гликопротеина СА-62 во всех изученных эпителиальных карциномах различных локализаций, таких как молочная железа, простата, легкие, желудок, кишка и яичники [14][15][16]. Однако, несмотря на проявление маркера СА-62 в различных злокачественных новообразованиях эпителиального генеза, он обладает онкоспецифичностью (более 90 %) при сравнении злокачественных новообразований с доброкачественными заболеваниями и данными условно здоровых субъектов.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…На клеточной мембране таких низкодифференцированных мезенхимальных стволовых клеток с самого начала канцерогенеза в больших количествах образуется сильно гликозилированный гликопротеин СА-62, который попадает в кровь с поверхности клеток на самых ранних стадиях рака, включая карциномы in situ, и детектируется при помощи ИХА-СА-62 хемилюминесцентного иммуноанализа. Более ранние исследования показали, что злокачественные клетки демонстрируют значительную экспрессию гликопротеина СА-62 во всех изученных эпителиальных карциномах различных локализаций, таких как молочная железа, простата, легкие, желудок, кишка и яичники [14][15][16]. Однако, несмотря на проявление маркера СА-62 в различных злокачественных новообразованиях эпителиального генеза, он обладает онкоспецифичностью (более 90 %) при сравнении злокачественных новообразований с доброкачественными заболеваниями и данными условно здоровых субъектов.…”
Section: Discussionunclassified
“…med.). 2023; 10(1): [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. https://doi.org/10.17709/2410-1893-2023-10-1-1, EDN: JVPCQC Research and Practical Medicine Journal.…”
mentioning
confidence: 99%
“…Authors ( 16 , 17 ) revealed that a CA-62 marker associated with epithelial tumors can be significantly expressed and detected to varying degrees in the tissues of malignant tumors (such as breast, prostate, lung, uterus, stomach, kidney, colon, and ovaries), as well as in various human biological fluids (including blood and saliva). At the same time, healthy control subjects do not demonstrate increased expression of the CA-62 marker.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells release into the blood two main soluble cytoplasmic fractions of N-glycoprotein that are detected by the antibody used in the test. This allows to quantitatively measure a serum level of CA-62 antigen using a specific chemiluminescent assay CLIA-CA-62 intended to help with the medical decision-making process and recommended for early cancer detection in combination with clinical data and other diagnostic procedures ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation